2017
DOI: 10.1177/1525740117716416
|View full text |Cite
|
Sign up to set email alerts
|

A Multicomponent Writing Intervention for a College Student With Mild Brain Injury

Abstract: Students sustaining mild traumatic brain injuries (mTBIs) face a variety of physical and cognitive difficulties immediately postinjury. Most students overcome these difficulties within a few months, but a portion experience long-term effects (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Explicit instruction or feedback has been documented as an effective teaching strategy for students with TBI (Kennedy et al, 2008b). Dinnes & Hux (2018) developed a multicomponent writing intervention using this approach. The intervention provided opportunities for the participant to practice semantic associations, semantic mapping, proofreading, written organization, foundational skills, and developing writing goals.…”
Section: Essay Writing Interventionsmentioning
confidence: 99%
“…Explicit instruction or feedback has been documented as an effective teaching strategy for students with TBI (Kennedy et al, 2008b). Dinnes & Hux (2018) developed a multicomponent writing intervention using this approach. The intervention provided opportunities for the participant to practice semantic associations, semantic mapping, proofreading, written organization, foundational skills, and developing writing goals.…”
Section: Essay Writing Interventionsmentioning
confidence: 99%
“…Emerging research also describes deficits in auditory comprehension, verbal expression, reading, writing, and social communication. [17][18][19][20][21] While these cognitive-linguistic areas of need parallel deficits in more severe forms of TBI, clinicians struggle with best practices for assessment. A recent study indicated that SLPs report feeling most uncomfortable with assessment of TBI over all other TBI-related clinical tasks.…”
mentioning
confidence: 99%